The Effect of PBL Learning Model on Students Mathematic Learning Outcomes at Social Arithmetic in MTs - Sholahudin Al Ayubi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
The purpose of the research is to know the effect of PBL model to the student mathematic learning outcomes. The type of the research is exsperimental research with quantitative approach. The subject of this research is a seventh grade student’s in MTs Ainul Yaqin. The subjects are given the test to know mathematic learning outcomes. The data collecting methods are documentation and test method. The results of the research are the value of chi square product = 45.000 and chi square table = 3.481 it’s mean that chi square product > chi square table so Ha is accepted and Ho is rejected. The conclusion there is significant effect of using PBL model to the student mathematic learning outcomes in seventh grade student of MTs Ainul Yaqin on Aritmetika Social material. The suggestion is the teacher must use innovative learning model that can make student active to carry, find and make conclusion about the problem.  Keywords: PBL, mathematical learning outcomes